IMPLEMENTASI METODE DMAIC (DEFINE, MEASURE,ANALYZE, IMPROVE, CONTROL) UNTUK MENURUNKAN CACAT BONDING SEPATU DI GEDUNG 2 (DUA) PADA PT. PARKLAND WORLD INDONESIA - Suci Terawati; Wahyu Wiguna (Universitas Bina Bangsa, 2021)
This study focuses on how to control defective products at PT. Parkland World Indonesia, a company engaged in the Adidas brand shoe industry for the period April 2020 to March 2021, the average product achievement reaches 8.37%, while the company wants Zero Defect. The purpose of this study is to reduce bond defects through an approximation approach, where we observe and conduct tests in order to improve performance and reduce. The method to guarantee the quality of the product produced is DMAIC (Define, Measure, Analyze, Improve, Control) which is a data-based problem solving approach that helps to optimally correct defects caused by the production process can decrease. The results of the analyzed data showed 5 CTQ (Critical to Quality) bonds with the highest percentage of bonding stabilizer at 43.70%. The conclusions and recommendations that can be drawn from this study are the causes of shoe ties that can be prevented by implementing several proposed improvements, by providing the latest SOPs, maximum WIP visual standards, brush change visual systems, and providing RCA (root cause analysis) board meetings